Pradhan Mantri Janjati Adivasi Nyaya Maha Abhiyan (PM JANMAN): An Endeavor to reach the unreached for improving Healthcare of Tribals in India - Joshi, Abhishek Upendra; Raut, Juhi Mangesh (Indian Journal of Community Health, 2024)
One hundred and four Million tribal people live in India, which accounts for 8.6% of the country’s population. The Union Cabinet on 15th November 2023 approved the Pradhan Mantri Janjati Adivasi Nyaya Maha Abhiyan (PM-JANMAN) aiming to reach out to over twenty-two thousand particularly vulnerable Tribal groups (PVTG) tribal habitats over two hundred districts in India. It focuses on the key elements of improving housing and lifestyle, education status, roads and connectivity, livelihood, and the healthcare sector. As per the report of the Expert Committee on Tribal Health, the tribal population in the country faces a triple burden of diseases, some of which are indirectly addressed in this initiative. Other major concerns like alcohol addiction and animal and snake bites have been left out, which could have gone a long way in mitigating these concerns among the tribal population. This initiative if implemented properly will revolutionize the health situation in the tribal communities across the country.